2019
DOI: 10.3389/fpsyg.2019.00654
|View full text |Cite
|
Sign up to set email alerts
|

Race Strategies of Open Water Swimmers in the 5-km, 10-km, and 25-km Races of the 2017 FINA World Swimming Championships

Abstract: Despite literature on the pacing strategies of endurance sports, there is an existing lack of knowledge about the swimmers’ tactical decisions in the open water races. The aims of the present research were (1) to compare the pacing profiles and tactical strategies of successful elite open water swimmers (men and women) in the 5-km, 10-km, and 25-km races and (2) to relate these pacing strategies to the end race results. Intermediate split times, positions and gaps with leaders of the first ten swimmers classif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 35 publications
1
27
0
Order By: Relevance
“…In addition to pool-swimming events, open-water swims were held as individual swims (i.e., solo swims in Channel Crossings without drafting) or competitions in long-distance swimming events up to 25 km in open-water swimming [10,15] where swimmers are allowed to swim in a group and where drafting is allowed. In addition, there were open-water swimming events of different lengths in lakes and seas [7] where drafting is also allowed.…”
Section: Open-water Swimmingmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to pool-swimming events, open-water swims were held as individual swims (i.e., solo swims in Channel Crossings without drafting) or competitions in long-distance swimming events up to 25 km in open-water swimming [10,15] where swimmers are allowed to swim in a group and where drafting is allowed. In addition, there were open-water swimming events of different lengths in lakes and seas [7] where drafting is also allowed.…”
Section: Open-water Swimmingmentioning
confidence: 99%
“…Indoor-swimming events with a defined time limit (i.e., 12 h) are also held [13]. In open-water swimming, master swimmers most often compete in 3000 m [14], whereas 5 km [6,10], 10 km [10,15] and 25 km [10,15] races were held for elite swimmers. Open-water swimming events of different lengths in lakes and seas are held as solo swims [7].…”
Section: Introductionmentioning
confidence: 99%
“…I suggest the end-spurt and the related U-shape patterns in pacing stem from a simple motivational mechanism – perceived impact: the perceived extent by which one’s actions influence goal-progress. This mechanism is demonstrated in everyday lives and in competitive sports (e.g., when consumers walk toward the end of an aisle in a supermarket; Van Den Bergh et al, 2016; Open-water swimmers during the world championship; Veiga et al, 2019). Indeed, exercise scientists previously suggested that the end-spurt mostly stems from psychological rather than physiological mechanisms (e.g., centrally induced fatigue, perception of effort, concious experience; Noakes, 2012; Smirmaul et al, 2013; Renfree et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In open-water swimming, most often events over 3, 5, 10 and 25 km are held. The 5, 10 and 25 km are held as official FINA (Fédération Internationale de Natation) races for elite swimmers (Baldassarre, Bonifazi, Zamparo, & Piacentini, 2017;Veiga, Rodriguez, González-Frutos, & Navandar, 2019) whereas the 3 km are especially designed for master swimmers (Knechtle, Nikolaidis, Rosemann, & Rüst, 2017a).…”
Section: Introductionmentioning
confidence: 99%